2016
DOI: 10.1080/01635581.2016.1190022
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed Sex Hormone Biosynthesis by Alkylresorcinols: A Possible Link to Chemoprevention

Abstract: Alkylresorcinols (ARs, 5-n-alkylresorcinols) are amphiphilic phenolic lipids in whole grain rye and wheat, with a long odd-numbered carbon chain. A preventive effect of whole grain diet on sex hormone-dependent cancers has been recognized, but the active component(s) or mechanisms are not known. We have investigated the effects of the ARs C15:0, C19:0, and C21:0, individually and in combination, on steroid hormone production by using the human adrenocortical cell line H295R. Decreased synthesis of dehydroepian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In the study of Oskarsson and Ohlsson [ 72 ] carried out on the human adrenocortical cell line H295R, the nontoxic concentrations of C15 : 0 and C19 : 0 ARs directly affected the steroidogenesis; namely, they reduced the synthesis of testosterone and decreased the secretion of estradiol, cortisol, and aldosterone. The authors proposed that the decline in the secretion of the hormones could appear due to the inhibition of the activity of CYP17 enzyme, which is in charge of the conversion of pregnenolone to 17 α -OH-pregnenolone and of progesterone to 17a-OH-progesterone.…”
Section: The Biological Effects Of Arsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Oskarsson and Ohlsson [ 72 ] carried out on the human adrenocortical cell line H295R, the nontoxic concentrations of C15 : 0 and C19 : 0 ARs directly affected the steroidogenesis; namely, they reduced the synthesis of testosterone and decreased the secretion of estradiol, cortisol, and aldosterone. The authors proposed that the decline in the secretion of the hormones could appear due to the inhibition of the activity of CYP17 enzyme, which is in charge of the conversion of pregnenolone to 17 α -OH-pregnenolone and of progesterone to 17a-OH-progesterone.…”
Section: The Biological Effects Of Arsmentioning
confidence: 99%
“…Along with ARs leading to decreased plasma estrogen levels, the generally high dietary fiber intake was reported to be associated with the lower risk of breast cancer as well [ 78 , 79 ]. Besides the mechanism described earlier, ARs, as highly lipophilic molecules, are proposed to affect steroid hormone production through the accumulation in tissues enriched in lipids, such as adipose tissue, testis, ovaries, and adrenal cortex, which are in charge of steroidogenesis [ 72 ].…”
Section: The Biological Effects Of Arsmentioning
confidence: 99%
“…Importantly, the separated alkylresorcinols had an inhibitory impact on the breast cancer cell line examined that was at least 800% greater than the routinely used chemotherapy, adriamycin. In another study to examine the mechanism of alkylresorcinols [ 99 ], it has been found that alkylrespocinols suppressed the expression of CYP21A2, HSD3B2, and CYP19A1 genes, while increased the expression of CYP11A1. The impacts on steroidogenesis could not be explained by gene expression data, which might be attributable to direct effects on enzyme activities, such as suppression of CYP17A1.…”
Section: Resultsmentioning
confidence: 99%
“…Adipose tissue in the breast is one of the main sites of sex hormone production in post-menopausal women [86,87]. Short alkylresorcinol homolog exposure of adipose tissue through storage in its adipocytes or in postprandial blood [43] may alter sex hormone synthesis by promoting the synthesis of progestogens from cholesterol and suppressing downstream metabolism of progestogens and estradiol, as shown in vitro [78]. A high concentration of these sex hormones is strongly associated with risk of breast cancer [88].…”
Section: Discussionmentioning
confidence: 99%
“…In a secondary analysis, we also assessed the risk of developing breast cancer using short alkylresorcinol homologs (C17:0, C19:0 or C21:0) as exposure in Crude biomarker models and Multivariate-adjusted biomarker models. This was because alkylresorcinol homologs shorter than C21:0 have been shown to suppress synthesis of sex hormones [78] and because the C17:0/C21:0 ratio is potentially affected by C17:0, C21:0, or both.…”
Section: Methodsmentioning
confidence: 99%